Isolated cardiac sarcoidosis: a case report - I. A. Skomkina; V. F. Mordovin; S. V. Triss; I. V. Stepanov; N. I. Ryumshina; M. A. Polyakova; R. E. Batalov; A. Yu. Falkovskaya (Российский кардиологический журнал)
Introduction. Ventricular arrhythmias are a risk factor for sudden cardiac death. Abnormalities of cardiac rhythm and conduction may be the only subjective manifestation of isolated cardiac sarcoidosis, which occurs in 25% of the total number of patients with this disease.Brief description. We present a case of isolated cardiac sarcoidosis in a young female patient, the main clinical manifestation of which was attacks of palpitations caused by ventricular tachycardia and episodes of cardiogenic shock without a cardiovascular history. Echocardiography and contrast-enhanced cardiac magnetic resonance imaging (MRI) revealed asymmetric left ventricular hypertrophy and focal myocardial masses. Cardiac tumor and sarcoidosis were suspected. The final diagnosis was based on the results of histological and immunohistochemical analysis of endomyocardial biopsies documenting sarcoidosis. No systemic manifestations of sarcoidosis were found.Discussion. The case demonstrates the potential of a comprehensive paraclinical study in the diagnosis of cardiac sarcoidosis and its differential diagnosis with other cardiac pathologies.Conclusion. Cardiac sarcoidosis is difficult to diagnose and requires histological verification in patients with LV hypertrophy and arrhythmias, and physicians should be aware about this rare disease with unfavorable prognosis without specific treatment.